Existence Results of Langevin Equations with Caputo–Hadamard Fractional Operator - Sombir Dhaniya; Anoop Kumar; Aziz Khan; Thabet Abdeljawad; Manar A. Alqudah (Journal of Mathematics)
In this manuscript, we deal with a nonlinear Langevin fractional differential equation that involves the Caputo–Hadamard and Caputo fractional operators, with nonperiodic and nonlocal integral boundary conditions. The results presented in this study establish the existence, uniqueness, and Hyers–Ulam (HU) stability of the solution to the proposed equation. We achieved our main result by using the Banach contraction mapping principle and Krasonoselskii’s fixed point theorem. Furthermore, we introduce an application to demonstrate the validity of the results of our findings.